PHYTOCHEMICAL COMPOSITION IN Moringa oleifera - K. SURENDRA GOPAL; BERIN PATHROSE, K. A. ATHIRA, SEEJA THOMACHAN, E. R. ANEENA, C. L. SHARON (The Journal of Research, PJTSAU, 2023)
Moringa oleifera, known as drumstick tree is widely cultivated throughout India. It is widely used as a nutritive herb and possess valuable pharmacological activities. Due to its amazing abilities for various ailments and even some chronic diseases, it is also named as “the miracle tree”. Phytochemicals are chemical compounds that are naturally found in plant. Phytochemicals could be available as a dietary supplement, but the potential health benefits of phytochemicals are derived from consumption of the whole plant. Non-nutritive plant compounds with disease preventive or protective characteristics are known as phytochemicals. Seasonal variability of primary and secondary metabolites in moringa leaves evaluated in the month of July-August through LC-MS/MS (non-volatile) and GC-MS/MS (volatile) technique. Non-volatile toxic compounds identified were adenosine, oligomycin C, euphormin and umbelliferone present in the month of July-August. Volatile compounds identified during this period were morphinan and dihydromorphine. The compounds hematoporphyrin, euphormin and umbeliferone are intermediates in cyanide pathway during July-August and it effects the human health causing nausea, vomiting and gastrointestinal disturbances.